A Comparative Study of Efficiency between Conventional and Islamic Banks in Indonesia - Havidz, Shinta Amalina Hazrati; Setiawan, Chandra (Asian Economic and Financial Review, 2015)
This paper investigates the bank efficiency as a basis performance measurement in the Conventional and Islamic banks in Indonesia in the period of January 2008 – September 2013 using quarterly-published report data of Central Bank (Bank Indonesia) with 6 Conventional banks and 3 Islamic banks in Indonesia as the samples of the research. The Bank efficiency in this research is measured using financial ratios and macroeconomics as determinants of Return on Assets (ROA) and non-parametric approach DEA (Data Envelopment Analysis). In term of variables that determine ROA using panel least square by estimating Fixed Effect Method (FEM), the findings reveal that there are significant effects of Loans to deposit ratio (LDR), Operational efficiency ratio (OER) and GDP growth rate to ROA and there are no significant effects of Capital Adequacy ratio (CAR), Size and inflation rate in the Conventional banks in Indonesia. On the other hand, all the independent variables have significant effect to ROA, except financing to deposit ratio (FDR) in the Islamic banks in Indonesia. GDP growth rate is the highest coefficient among the determinant variables used in this research that affect ROA of both Conventional and Islamic banks and the weakest coefficient that affects ROA is CAR in the Conventional banks and FDR in the Islamic banks. The findings of DEA indicate that the bank inefficiency is caused of not-well function of banks and managers of banks are not able to use the firms’ given resources.